Inflammation, peripheral signals and redox homeostasis in athletes who practice different sports - Luti, S.; Modesti, A.; Modesti, P. A. (antioxidants, 2020)
The importance of training in regulating body mass and performance is well known. Physical training induces metabolic changes in the organism, leading to the activation of adaptive mechanisms aimed at establishing a new dynamic equilibrium. However, exercise can have both positive and negative effects on inflammatory and redox statuses. In recent years, attention has focused on the regulation of energy homeostasis and most studies have reported the involvement ofperipheral signals in influencing energy and even inflammatory homeostasis due to overtraining syndrome. Among these, leptin, adiponectin, ghrelin, interleukin-6 (IL6), interleukin-1ß (IL1ß) and tumour necrosis factor a (TNFa) were reported to influence energy and even inflammatory homeostasis. However, most studies were performed on sedentary individuals undergoing an aerobic training program. Therefore, the purpose of this review was to focus on high-performance exercise studies performed in athletes to correlate peripheral mediators and key inflammation markers with physiological and pathological conditions in different sports such as basketball, soccer, swimming and cycling.